Cultural rights of native majorities between universalism and minority rights - Ruud Koopmans (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Minorities' claims for rights increasingly clash with majorities who wish to retain and defend "national" cultural and religious traditions. Debates around minarets in Switzerland, burqas in France, Saint Nicolas' companion "Black Pete" in the Netherlands, and about freedom of speech versus respect for minorities in several countries are cases in point. Such issues are highly salient and offer a major mobilization potential for populist parties. However, while publications about minority rights abound, the normative literature is remarkably silent on the issue of the normative legitimacy of rights claims by autochthonous cultural majorities. The reason for this negligence is the assumption that majorities can, by definition, impose their will by electoral force. But in the postwar rights regime in which protection for minority rights has proliferated, there are many situations in which parliamentary majorities have been trumped by court decisions or obligations derived from international treaties. Moreover, even if electoral majorities prevail, this does not solve the normative problem and leads to situations in which claims of minorities, legitimated by national and supranational minority protection norms, stand against majorities backed by the electoral power of numbers but lacking normative legitimacy. The paper argues that it is this dynamic of "right" versus "might" that is an important structural factor behind the rise of nationalist populism across Western countries. This confrontation has a tendency to polarize and to escalate, because there is no common normative ground on which the legitimacy and limits of majority rights claims can be negotiated. For one side in such debates, majorities have no legitimate right whatsoever to claim privileges for their language or culture over others, for the other side, this right is absolute because in the populist view democratic legitimacy is reduced to whatever the majority decides. A normative elaboration of the legitimacy and limits of cultural majority claims is necessary to escape from this confrontation that increasingly poisons the political debate in Western democracies. An additional reason to take cultural majority rights more strongly into consideration is that the idea that majority cultures are not in need of any special protection is less and less tenable. In a more and more globalized world where Anglo-Saxon culture has become the norm in many domains, the distinction between "dominant" and "minority cultures" can no longer be exclusively seen as applying to relationships within nation-states, but increasingly also applies to the unequal balance of power between the cultures of nation-states.
Keywords: 300; majority rights; self-determination; immigration; indigenous peoples; populism; multiculturalism